Xylariaceae fimicolas: Xylaria equina sp. Nov. and new Mexican records of Xylaria pileiformis and Poronia erici - San Martin, Felipe; Lavin, Pablo; Perez Silva, Evangelina (Instituto de Ecología, A.C., 1998)
Poronia erici is first recorded for the American continente and a key is provided for Poronia species currently known from Mexico. Xylaria pileiformis is first recorded for the Mexican mycobiota. Xylaria equina is proposed as new to science and is compared with other fimicolous and non fimicolous species of the genus. A key is given to five coprophilous Xylaria species.